Mechanism on M (MNi, Mo, NiMo) as deep level impurity reducing the TCR of Si-rich CrSi resistive films. (September 2017) - Wang, X.Y.; Liu, Y.P.; Ding, B.N.; Li, M.X.; Chen, T.N.; Zhu, X.T.
Abstract: CrSi–M (MNi, Mo, NiMo) resistive films were prepared by magnetron sputtering technique at the same process conditions. Experimental results shows that the metal M can reduce the temperature coefficient of resistance (TCR) of Si-rich CrSi resistive films, and that the resistive films follow the sequence of CrSiMo (6.34 at%) < CrSiNi (9.97 at%) < CrSiNi (6.08 at%)Mo (2.47 at%) according to TCR tending to zero. XRD analysis reveals that CrSi2 is the main conductive phase in the prepared CrSi–M resistive films. In order to explore the reasons that M can reduce the TCR of Si-rich CrSi resistive films, first principles was used to study the influence of M on the performance of CrSi2 from state density and band structure. The first-principles study on M-doped CrSi2 shows that M may exist in CrSi2 semiconductor in the form of deep level impurity, and an energy band model on both Ni and Mo-doped CrSi2 is constructed to reflect the results of first-principles simulation. Based on the established model, a mechanism is proposed that deep level impurities as electron traps capturing electrons and the formation of tight-binding excitons can suppress the non-equilibrium hot carriers against being contributed to the conductivity of CrSi2 semiconductor. As a result, the TCR of Si-rich CrSi resistive films is reduced due to the doping of M as deep level impurity. Highlights: CrSi–M (MNi, Mo, NiMo) films were prepared at the same process conditions. CrSi2 is the main conductive phase in CrSi–M film. Non-equilibrium hot carriers make pure CrSi films have a high negative TCR. M as deep-level impurity in CrSi2 can capture thermally excited electrons. M can suppress non-equilibrium hot carriers due to tightly bound excitons.